Presentation Analysis Element Linguistics in Textbook for Language Teaching Arabic or Non-Arabic Speakers - Yayan Umyanah; Moch Muizzuddin; Siti Shalihah (FKIP - Universitas Riau, 2026)
Arabic language textbooks play a central role in developing student’s linguistic competence, particularly for non-native learners at the secondary education level. This study aims to analyze the presentation of linguistic elements in the Grade XI Arabic language textbook published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020. Using a qualitative content analysis approach, the research examined three thematic chapters: Shopping, Health, and Journey. The analysis focused on six linguistic components: phonology, morphology, syntax, semantics, pragmatics, and stylistics. Findings indicate that phonology, morphology, syntax, and semantics are consistently presented through listening activities, grammatical explanations, dialogues, reading texts, and vocabulary development. Morphological and syntactic elements are explicitly integrated through qawa'id sections, while semantic aspects are reinforced through contextualized vocabulary and meaning interpretation. However, phonological coverage remains limited, as the textbook does not provide explanations of Arabic sound production, including articulation points and sound characteristics. Furthermore, pragmatic and stylistic elements are not explicitly incorporated, reducing opportunities for learners to develop sociocultural awareness and communicative appropriateness. These findings suggest that the textbook effectively supports foundational linguistic competence and language learning for non-native Arabic learners. Nevertheless, supplementary instructional materials and teacher intervention remain essential for achieving comprehensive language acquisition.